Examining the role of solar activity, climate, and the socio‐historical context in high all‐cause mortality (northern Portugal, 1700–1880). (25th October 2021) - Moreno, João; Moreno, Filipa; Fatela, Francisco; Leorri, Eduardo
Abstract : The far‐reaching impact of the Sun on Earth's climate and on people's health and well‐being is a poorly understood and non‐consensual scientific issue, with empirical literature stressing the need to expand the knowledge of such relationships. Here, the interplay between solar activity (SA) and climate, and its likely cascading effects on all‐cause mortality, were examined at several time scales. To this end, the parish records of Braga (1700–1880) and Torre de Moncorvo (1700–1850), in two different geographical locations of northern Portugal (Iberia, SW Europe), were used. Crude mortality rate (CMR) and winter–summer ratio (W/S) values were computed to characterize mortality patterns/trends and couple them with potential relevant drivers: total solar irradiance (TSI) as a proxy of SA, the North Atlantic Oscillation (NAO), and key historical events. What emerged, albeit incomplete, was a complex picture of death deeply embedded in people's physical and socioeconomic environments, at a time when ubiquitous poverty (and co‐morbid malnutrition) was the most inveterate cause of ill health. After identifying the positive mortality episodes in both municipalities, their incidence was found to be higher in periods of weakened SA (normal/grand minima). Standard inference statistics were used to estimate the significance of the observations. The highest CMR peaks matched not only with wars but also with known wide‐ranging mortality crises, which seem to have been triggered by major agricultural production shortfalls, followed by substantial increases in food prices, driven, in turn, by climate deterioration, including extreme weather occurrences. The outcome was social unrest, famines, and outbreaks of infectious diseases, heightening the death toll. The influence of prominent solar/climate variations was investigated using wavelet transform coherence analysis (WTC). The results showed (multi)decadal oscillations in both (TSI and NAO) somehow regulating mortality. But the WTC analysis also estimated SA signals in low‐frequency mortality dynamics disguised by time‐varying determinants, where distinct players of space weather might have been implicated.